2012
DOI: 10.1179/102453312x13336169156618
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor (VWF) as a risk factor for bleeding and thrombosis

Abstract: The von Willebrand factor (VWF) is analysed as a bleeding and thrombotic risk marker. When the VWF level is increased, it predicts a thrombotic phenotype and when VWF level is low in plasma, the phenotype varies to bleeding disorder. But it is quite challenging to define when the level is low, normal or high taking into account that these values are capricious and overlap. This matter should be solved by extensive epidemiologic studies. VWD is a hereditary disorder with several described mutations. VWF is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The reciprocal also holds true, with a higher incidence of thrombosis in nongroup O individuals . This may be related to the 25% lower levels of von Willebrand Factor in individuals with blood group O vs. non‐O . An argument for a higher bleeding tendency per se in blood group O patients is the nonsignificant higher blood transfusion rate in blood group O ABOc controls and the finding that only blood group O patients received more than one blood transfusion in controls.…”
Section: Discussionmentioning
confidence: 93%
“…The reciprocal also holds true, with a higher incidence of thrombosis in nongroup O individuals . This may be related to the 25% lower levels of von Willebrand Factor in individuals with blood group O vs. non‐O . An argument for a higher bleeding tendency per se in blood group O patients is the nonsignificant higher blood transfusion rate in blood group O ABOc controls and the finding that only blood group O patients received more than one blood transfusion in controls.…”
Section: Discussionmentioning
confidence: 93%
“…Secreted from activated endothelial cells, von Willebrand factor (VWF) is a key endothelial player participating in both platelet aggregation and the regulation of coagulation FVIII levels in the blood (Vischer, ). Increased plasma levels of VWF are associated with increased risk of VTE (Lazzari et al , ), making any genetic variation controlling the regulation of plasma VWF levels an obvious candidate for VTE. The latest genome‐wide association study (GWAS) for VWF levels revealed 8 loci that are associated with VWF levels (Smith et al , ).…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%
“…The final addition of novel biomarker GDF‐15 was crucial because this marker has a proven strong association with bleeding outcomes 8. A low circulating level of the endothelial activation marker vWF is a risk factor for bleeding 25. Osteoprotegerin binds vWF with high affinity, and this complex is present in vivo and may influence bleeding risk 2, 3.…”
Section: Discussionmentioning
confidence: 99%
“…8 A low circulating level of the endothelial activation marker vWF is a risk factor for bleeding. 25 Osteoprotegerin binds vWF with high affinity, and this complex is present in vivo and may influence bleeding risk. 2,3 In addition, osteoprotegerin may bind vWF reductase, thrombospondin-1, and in late stages of thrombus formation, this interaction may promote proteolysis of vWF multimers and prevent platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%